Disturbance of nitric oxide synthase constitutive isoforms expression as a pathogenetic factor of complications development after tooth extraction in experimental diabetes mellitus - K. S. Hanchev; A. V. Abramov (Zaporozhye State Medical University, 2018)
The role of constitutive NOS isoforms (endothelial and neuronal) in pathogenesis of complications development and repair processes disturbances in periodontium after tooth extraction in experimental diabetes mellitus is not studied completely. The aim of work - to find out the features of constitutive NOS isoforms (endothelial and neuronal) indices alterations in periodontal tissue of rats with experimental streptozotocin-induced diabetes mellitus on different terms (1st , 7th and 14th day) after mandibular 1st molar extraction. Materials and methods. Immunohistochemical study of endothelial and neuronal NOS isoforms expression indices (content, concentration, area of immunoreactive material distribution) in periodontium tissue was conducted on 120 male rats 8-10 months-old (8 experimental groups). Results. In rats with experimental diabetes mellitus (EDM) without tooth extraction content and concentration of both constitutive NOS isoforms in periodontium were lower than in control group of animals. The extraction of tooth in rats with EDM resulted in significant increase of all indices of both isoforms expression in comparison with EDM rats without tooth extraction. On the 7th day after tooth extraction nNOS content and area of distribution was also increased by 24.3 % and 14.2 % respectively, and concentration decreased by 58.3 %. Indices of eNOS were not reliably changed in comparison with the 1st day after tooth extraction. On the 14th day after tooth extraction in rats with EDM, a significant decrease in all the indices of expression of constitutive NOS was observed, moreover, the concentration and area of nNOS distribution and the content, concentration and area of eNOS become significantly lower than in the corresponding control group. Conclusions. In rats with EDM in periodontal tissues the content and concentration of NOS constitutive isoforms are reduced. Extraction of the tooth in the animal with EDM leads to a moderate increase in the content and concentration of nNOS and eNOS from the 1st to the 7th day. On the 14th day after the extraction, the expression indices of both isoforms decrease lower than in the corresponding control groups, that indicates a low content of endothelial and neuronal isoforms in the periodontium of rats with EDM and probably plays an important role in the pathogenesis of long-term complications development after surgery along with violation of repair processes.